Analysis of Credit Marketing Strategy, Lending Procedures, and Service Quality on Customer Satisfaction of Rural Banks - Mahjudin; Achmad Daeng G. S.; Enny Istanti (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Customer satisfaction plays a critical role in the long-term success and survival of any institution, and local banks, including Rural Banks, understand that their loan marketing strategies, lending practices, and the quality of service they offer are key drivers of customer satisfaction. This study aims to analyze the credit marketing strategies, lending procedures, and service quality of Rural Credit Banks in order to enhance customer satisfaction and explore the complex relationship between these factors and customer satisfaction. Using a quantitative approach, this study collected data through questionnaires distributed to a sample of 96 customers who applied for loans at Rural Banks. The findings revealed that personalized sales promotions, product displays, promotional programs, and public relations are fundamental to the credit marketing strategies of Rural Banks. The loan origination process consists of several steps, including file submission, loan file inspection, decision making, contract signing, loan disbursement, installment processing, and loan repayment. In addition, the study emphasized that competitive interest rates for small loans, combined with flexible repayment options based on membership levels, contribute significantly to customer satisfaction. Overall, this underscores the important role of loan marketing strategies, lending practices, and service quality in shaping customer satisfaction in the local banking context.